Sistem Informasi Absensi Siswa Pada SMK An Nur Berbasis Android Menggunakan Metode Spiral - Ray Diphan; Tri Rahmawati; Willa Agustin; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
School attendance is an important aspect in managing student attendance. Effective and efficient attendance data collection provides great benefits for schools in managing student attendance, monitoring the regularity of teaching and learning activities, and ensuring compliance with school policies. However, SMK AN NUR Depok attendance system is still done manually, starting from recording attendance data to making reports that often cause errors so that report making becomes inaccurate. Other problems, namely many occur in document storage such as frequent loss of data or archives. The creation of this attendance system uses data collection methods from SMK AN NUR Depok, field supervisor interviews, literature studies that support problem solving and Entity Relationship Diagrams (ERD) to document the needs for database processing systems and software testing using the spiral method.The purpose of this practical work is to design an information system to solve these problems. The results and benefits of this design are to provide facilities for teachers to take attendance on students so that attendance data processing becomes more structured and reduces the risk of errors in student attendance data. In addition, students can also check the attendance that has been inputted by the teacher.